Discovery of Posture Secret manual therapy for post-stroke shoulder pain: study protocol for a randomized controlled trial - Song, Chengning; Lei, Bo; Li, Zhixian; Li, Haiyan; Tian, Songting; Feng, Nana (Frontiers in Neurology, 2025)
BackgroundPost-stroke shoulder pain (PSSP) is a frequent complication that significantly impedes upper limb rehabilitation in stroke patients and contributes to global healthcare costs amounting to billions of dollars each year. Beyond the financial impact, PSSP severely compromises patients’ quality of life. Developing effective treatments to reduce pain and improve shoulder joint function in individuals with PSSP remains a pressing clinical priority. We are currently conducting a rigorously structured randomized controlled trial to evaluate and compare the effectiveness of Discovery of Posture Secret (DPS) therapy and Standardized Chinese Tuina Therapy (SCTT) in stroke patients diagnosed with shoulder pain through musculoskeletal ultrasound. This paper presents the trial’s design and implementation.Methods/designThis is a single-center, 4-week randomized controlled trial carried out at the Department of Rehabilitation, Fuyong People’s Hospital, Bao’an District, Shenzhen, Guangdong Province. The objective is to assess the comparative effectiveness of DPS and SCTT in patients with PSSP. Eligible participants are stroke survivors aged between 40 and 60 years who meet the diagnostic criteria for PSSP established in China. Participants will be randomly assigned to one of two treatment groups, receiving one 40 min session each weekday (Monday through Friday) for four consecutive weeks, with rest on weekends. The primary outcome is the change in pain intensity measured by the Visual Analog Scale (VAS) at 2 weeks, 4 weeks, and at a 1-month follow-up. Secondary outcomes include shoulder joint function and general functional recovery at 4 weeks, evaluated using shoulder range of motion (ROM), the absolute difference in vertical distance between the medial superior angle of the scapula and the second thoracic spinous process, musculoskeletal ultrasound findings, and the Modified Barthel Index (MBI).DiscussionThis is the first randomized trial to compare the effectiveness of DPS and SCTT in PSSP patients, with a one-month follow-up. We propose a carefully constructed randomized controlled trial that, for the first time, employs musculoskeletal ultrasound as an objective tool for assessing PSSP. This methodological advance aims to increase the objectivity and reliability of the outcome data. The results of this trial are expected to carry substantial public health relevance for the growing population affected by PSSP and may inform better treatment approaches and functional recovery strategies.Clinical trial registrationClinicalTrials.gov, identifier NCT06763796.